The roles of circRNA–miRNA–mRNA networks in the development and treatment of osteoporosis - Gao, Manqi; Zhang, Zhongkai; Sun, Jiabin; Li, Bo; Li, Yuan (Frontiers in Endocrinology, 2022)
Osteoporosis is a systemic metabolic disease, mainly characterized by reduced bone mineral density and destruction of bone tissue microstructure. However, the molecular mechanisms of osteoporosis need further investigation and exploration. Increasing studies have reported that circular RNAs (circRNAs), a novel type of RNA molecules, play crucial roles in various physiological and pathological processes and bone related diseases. Based on an in-depth understanding of their roles in bone development, we summarized the multiple regulatory roles and underlying mechanisms of circRNA-miRNA-mRNA networks in the treatment of osteoporosis, associated with bone marrow mesenchymal stem cells (BMSCs), osteoblasts and osteoclasts. Deeper insights into the vital roles of circRNA-miRNA-mRNA networks could provide new directions and insights for developing novel diagnostic biomarkers and therapeutic targets in the treatment of osteoporosis.